Medico-social conditions of educational activity, quality of life and aspects of psychophysiological adaptation of modern pupils and students: features of interrelation and their hygienic assessment - Tymoshchuk, O.V.; Serheta, I.V.; Malyshevska, О.S.; Melnyk , V.I.; Motriuk, V.B. (Medicni Perspektivi, 2023)
The purpose of the study is a comprehensive hygienic assessment of the relationship between medico-social conditions of educational activities, quality of life and adaptive capabilities of students. During the research conducted on the basis of 5 modern educational institutions of different types: university, college, specialized school, lyceum and school, the significant deviations of indicators of hygienic assessment of daily regimen of pupils and students from generally accepted normative values (p<0.05-0.001)were revealed, which, first of all, concerned the excess of the maximum allowable duration of their daily stay in educational institutions, the length of time required to complete homework, low levels of physical activity, etc. It was found that the highest levels of quality of life among boys and girls are recorded according to the scales of Physical Functioning (PF), Bodily Pain (BP) and Role-Physical (RP), the lowest ones were Mental Health (MH), Vitality (VT) and Social Functioning (SF). The relationships between the values that indicate the characteristics of quality of life and features of the psychophysiological adaptation of pupils and students were revealed. Moreover, the largest number of relationships (r=0.36-0.77; p<0.05-0.001) which characterize quality of life indicators belong to boys according to the scales of Physical Functioning (PF), Mental Health (MH), Vitality (VT) , Bodily Pain (BP); to girls – Bodily Pain (BP), Vitality (VT), Mental Health (MH), General Health (GH), Role-Emotional (RE). When determining the features of intersystem relationships between components of quality of life and indicators of psychophysiological functions, it was found that the closest relationship (r=0.37-0.99; p<0.05-0.001) is observed between the characteristics of the speed of visual-motor reactions, mobility and balance of nervous processes, coordination of movements and indicators of quality of life according to the scales of General Health (GH), Physical Functioning (PF), Social Functioning (SF) and Mental Health (MH).